Perancangan Interior “Hosanna Florist And Handycraft” Di Mojokerto - Andreas Eka Saputra M.; Andereas Pandu Setiawan (Intra, 2014)
Nowadays, people more realize about beauty. We can see it from every events which is held by people like birthday, wedding, thanksgiving, funeral, etc. Flowers are universal beauty. Because of that, flowers can be an alternative to answer individual needs of beauty. “Hosanna Florist and Handycraft” is one of famous florist in Mojokerto. The most important thing from the design’s shop is for change people’s mind set from florist as a flower shop become the answer of the beauty’s need. This florist interior design shows a modern naturalism style. Naturalism is shown from a flowers garden which can be seen from inside’s shop. It can make customers become comfort and being one with nature.